2006
DOI: 10.1002/ffj.1773
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of seed essential oils from Algerian Nigella sativa extracted by microwave and hydrodistillation

Abstract: Extraction of essential oil from Nigella sativa seed collected at two locations in the Sahara desert, Timimoun (T) and Adrar (A), has been conducted by hydrodistillation (HD) and a microwave distillation process (MD). The composition of the volatile oil was investigated by capillary gas chromatography and gas chromatography-mass spectrometry. Using the hydrodistillation, active compounds such as p-cymene (8.9 and 7.2% in T and A, respectively), 4-terpineol (0.6-8.9%), thymohydroquinone (6.1-12.2%), thymoquinon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(51 citation statements)
references
References 26 publications
6
42
2
1
Order By: Relevance
“…Seeds or their oils were claimed for medicinal applications dating back to the ancient Egyptians, Greeks and Romans (Benkaci- Ali et al 2007). In Islamic literature, Nigella sativa is considered as one of the greatest forms of healing medicine.…”
Section: Medicinal Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seeds or their oils were claimed for medicinal applications dating back to the ancient Egyptians, Greeks and Romans (Benkaci- Ali et al 2007). In Islamic literature, Nigella sativa is considered as one of the greatest forms of healing medicine.…”
Section: Medicinal Applicationsmentioning
confidence: 99%
“…2). Seeds are commonly known as black seed, black cumin (English) and habbatu sawda or habbatu el baraka (Arabic) (Benkaci- Ali et al 2007). …”
Section: Botanical Aspectsmentioning
confidence: 99%
“…Hydrodistillation using the Clevenger-type apparatus is the most commonly used technique for laboratory-scale extraction of essential oils [37][38][39].…”
Section: Hydrodistillationmentioning
confidence: 99%
“…The chemical profiles of these oils were compared by gas chromatography-mass spectrometry (GC-MS) and no major changes were observed between them [43]. Other recent examples are microwave extraction of Nigella sativa seeds [39], Carum ajowan (ajowan), C. cyminum and Illicium anisatum (star anise) [44].…”
Section: Supercritical Fluid Extractionmentioning
confidence: 99%
“…Kiralan et al [18] investigated the influence of extraction methods including MAE on the physicochemical properties and stability of black cumin seed oil (Nigella sativa), but bioactives were out of the scope of that study. Additionally, there have been studies investigating the extraction of essential oils and volatiles from black cumin seed by microwave-and hydro-distillation, the results of which revealed that microwave-assisted distillation provided a higher yield in shorter processing time with lower energy consumption [13,19]. Fig.…”
Section: Introductionmentioning
confidence: 99%